Relationship between Gender and Opinion Leadership among the Fish Farmers of Chhattisgarh - Ratre, Dileshwari; Ojha, S N; Sharma, Arpita; V., Ramasubramanian; Yadav, Rajpal (Indian Journal of Extension Education, 2021)
The ratio of fish farmers to fisheries extension professionals was 1:1000 which is too low. Para-extension functionaries can fill up this gap in the fisheries sector to improve theÂ production and productivity of fishers. The opinion leaders from the local fish farmersÂ community will help identify fish farmers who can further transfer the knowledge concerning how to fish to others through their diffusion network. This study was undertaken toÂ analyze gender roles in fish farming and their relation with opinion leaders. It was observedÂ that 90% of male fish farmers had control of fisheries/family resources, and 97 per cent of fish farmers were found to have contact with male opinion leaders. At the same time, 33%Â of female fish farmers were contacted by shelf help groups and local progressive farmers. The study shows that the opinion leaders influenced the fish farmersâ€™ diffusion networkÂ and their knowledge about how to fish. To involve women in the fisheries sector, empower women, there is also a need to select opinion leaders preferred by women fish farmers.